Identification of Traditional Herbal Leaves and Their Benefits Using K-Nearest Neighbors (KNN) - Nur Rahma Ditta Zahra; Kanaya Sabila Azzahra; Nur Iman Nugraha; Muhammad Ilham Nurfajri; Nabil Malik Al Hapid; Endang Purnama Giri; Gema Parasti Mindara (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Abstract. This study presents a web-based system for identifying traditional herbal leaves using K-Nearest Neighbors (KNN) and image processing techniques focused on analyzing leaf shape and color. The dataset used consists of images of various types of herbal leaves, providing a basis for classification and medicinal benefit information retrieval. The system was tested with multiple leaf samples to assess accuracy, speed, and effectiveness in identifying leaf types based on visual characteristics. Results show that the system can recognize different types of herbal leaves and display information on their medicinal properties in a user-friendly interface..